How to finance Eastern enlargement of the EU : the need to reform EU policies and the consequences for the net contributor balance - Christian Weise (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This paper analyses the consequences of the planned enlargement on the EU budget for the years 2007 and 2013. It concentrates on the EU's Common Agricultural Policy and Structural Policy and calculates the possible fiscal consequences of enlarging the EU for various policy scenarios. Enlarging the EU could be financed without overstepping the current upper limit for the EU budget, but it increases the pressure for EU policy reform. The main aim of such reforms is to reduce income support in agricultural policy and to concentrate structural policy on needy member states. These reforms would lead to a distribution of net burdens which was more strongly orientated according to the relative income of EU members. The burden for net contributors would remain under control, financial support for needy member states in the present EU would continue and new members would receive equal treatment from expenditure-related programmes.
Keywords: H87; P16; D78; F02; H11; 330; Enlargement; EU Budget; reform scenarios; Öffentlicher Haushalt; EU-Erweiterung; EU-Agrarpolitik; EU-Strukturfonds; Finanzausgleich; EU-Staaten; Osteuropa; Nettozahlerposition